Perversion Now! - Wright, Colin; Caine, Diana (Palgrave Macmillan, 2017)
This collection, written by leading Lacanian psychoanalytic theorists and practitioners, explores the impact of shifts in contemporary culture, politics and society on the notion of ‘perversion’, which has undergone numerous profound changes in recent years. The book explores a wide range of issues, from changes in the psychoanalytic clinic, to transformations in the relationship between ‘transgression’ and the law; from the epistemic and diagnostic status of ‘perversion’ as a term, to the perverse turn in contemporary politics; from representations of perversion in cultural productions, to the interpretation of perverse cultural practices. Topical and controversial, academics and students of psychoanalysis, critical and cultural theory, and media studies will find this collection invaluable. In providing cutting edge theoretical debate, the book will also be attractive to practising and training psychoanalysts and psychoanalytic psychotherapists.